2017
DOI: 10.3168/jds.2016-11828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dipeptidyl peptidase-IV inhibitory peptides from mare whey protein hydrolysates

Abstract: Inhibition of dipeptidyl peptidase-IV (DPP-IV) activity is a promising strategy for treatment of type 2 diabetes. In the current study, DPP-IV inhibitory peptides were identified from mare whey protein hydrolysates obtained by papain. The results showed that all the mare whey protein hydrolysates obtained at various hydrolysis durations possessed more potent DPP-IV inhibitory activity compared with intact whey protein. The 4-h hydrolysates showed the greatest DPP-IV inhibitory activity with half-maximal inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 40 publications
1
39
2
2
Order By: Relevance
“…For example, pepsin hydrolysates of α‐lactalbumin and bovine milk whey have IC 50 s of ~36–50 μg/mL and 70 μg/mL, respectively (Lacroix and Li‐Chan ; Nongonierma and FitzGerald, ), whereas a β‐lactoglobulin digested with trypsin has IC 50 s of 174 μM (Uchida et al ). Also, mare’s milk whey digested with papain for 4 h can generate peptide fragments with IC 50 of 180 μg/mL (Song et al ), which is 35% higher than the result obtained in this study (92.8670 μg/mL). Isolated milk serum hydrolysed with pepsin showed an IC 50 of 75 μg/mL (Lacroix and Li‐Chan ), an activity which is ~57% lower than that observed in this study.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…For example, pepsin hydrolysates of α‐lactalbumin and bovine milk whey have IC 50 s of ~36–50 μg/mL and 70 μg/mL, respectively (Lacroix and Li‐Chan ; Nongonierma and FitzGerald, ), whereas a β‐lactoglobulin digested with trypsin has IC 50 s of 174 μM (Uchida et al ). Also, mare’s milk whey digested with papain for 4 h can generate peptide fragments with IC 50 of 180 μg/mL (Song et al ), which is 35% higher than the result obtained in this study (92.8670 μg/mL). Isolated milk serum hydrolysed with pepsin showed an IC 50 of 75 μg/mL (Lacroix and Li‐Chan ), an activity which is ~57% lower than that observed in this study.…”
Section: Resultscontrasting
confidence: 77%
“…Once hydrolysates with high DPP‐IV inhibitory action have been identified, it is important to detect what peptides are responsible for such activity. For example, in the mare’s milk hydrolysates two oligopeptides with primary sequences of Asn‐Leu‐Glu‐Ile‐Ile‐Leu‐Arg and Thr‐Gln‐Met‐Val‐Asp‐Glu‐Glu‐Ile‐Met‐Glu‐Lys‐Phe‐Arg were identified, corresponding to β‐lactoglobulin F1 (71–77) and β‐lactoglobulin F1 (143–155), with IC 50 of 86.34 and 69.84 μM, respectively (Song et al ). Lacroix and Li‐Chan () reported that Leu‐Lys‐Pro‐Thr‐Pro‐Glu‐Gly‐Asp‐Leu and Leu‐Lys‐Pro‐Thr‐Pro‐Glu‐Gly‐Asp‐Leu‐Glu‐Ile‐Leu obtained from β‐lactoglobulin fraction were the most effective DPP‐IV inhibitors with activities of 45 and 57 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the peptide sequences provided in Table 3 , most of them were composed of the following amino acids: Pro, Phe, Gly, Leu, and Arg. According to Song et al [ 47 ], the first three residues were found as peptide constituents characteristic of DPP-IV inhibitors, whereas Arg (among others) can be found in the peptides acting as ACE inhibitors [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the peptide sequences provided in Table 3, most of them were composed of the following amino acids: Pro, Phe, Gly, Leu, and Arg. According to Song et al [47], the first three residues were found as peptide constituents characteristic of DPP-IV inhibitors, whereas Arg (among others) can be found in the peptides acting as ACE inhibitors [48]. 1 ACE i and DPP-IV i -angiotensin converting enzyme inhibitor and dipeptidyl peptidase IV inhibitor, respectively, 2 Pep-pepsin, 3 bold font-collagen hydrolysate source in which the peptide was identified more than once; 4 T-trypsin.…”
Section: Source Of Collagenmentioning
confidence: 99%
“…Combination of two or three of the above chromatography methods should achieve peptide purification. Song et al, Huang et al, and Ji et al combined gel filtration chromatography and C 18 chromatography to purify DPP-IV inhibitory peptides [37,38,39]. Harnedy et al used a C 18 matrix solid-phase extraction (SPE) column followed by Semipreparative reversed-phase high performance liquid chromatography (SP RP-HPLC) to obtain three purified DPP-IV inhibitory peptides [40].…”
Section: Methods For Discovering Food-derived Dpp-iv Inhibitory Pementioning
confidence: 99%